Pengaruh Penerapan Media Peta Pikiran dan Motivasi Belajar terhadap Hasil Belajar Ekonomi Siswa Kelas X IPS di SMA Negeri 1 Gunung Talang Kabupaten Solok - Basyirun, Fajri (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2016)
This study aims to find (1) Differences in learning outcomes of students who apply learning media mind map has a higher learning outcomes than the media board, (2) difference in students who have high motivation to learn higher learning outcomes of the students who have the motivation low learning, and (3) the interaction between the use of media mind map with motivation toward economics student learning outcomes. This type of research is quasi-experimental. The sampling technique was purposive sampling. The results of the study are (1) students are taught implement instructional media mind maps had significantly higher learning outcomes than students who were taught using the media blackboard with sig. = 0.001, is smaller than the value of ? = 0.05 (sig. <?), (2) high learning motivation students had significantly higher learning outcomes than students with low learning motivation with sig. = 0.001, is smaller than the value of ? = 0.05 (sig. <?) and (3) there is no interaction with the media use mind maps motivation on learning outcomes of students with sig. The mean value = 1.000 sig. Greater than the value of ? = 0.05 (sig.> ?). Based on these results, it is recommended that teachers use media mind maps on the learning process mainly on economic subjects.